Breakage Mechanism of Layered Sandstone Penetrated by TBM Disc Cutter - Yingji Bao; Jianlong Cheng; Binsong Jiang (Shock and Vibration)
In this paper, the breakage mechanism of layered sandstone subjected to the TBM disc cutter was investigated. A series of typical layered sandstone specimens were prepared for true triaxial compression tests in the laboratory to simulate the disc cutter action at the tunnel face, and an acoustic emission (AE) system was used to monitor the breaking process during the penetration tests. Furthermore, a DV recorder was employed to capture the surface deformation. Then, the failure specimens were scanned by high resolution X-ray micro-CT. The results show that the failure mode of layered sandstone in terms of cracking transforms into local crushing with increasing confining stress. The propagation pattern of the cracks varies with the bedding inclination, which is distinctly different from intact rock. The results also indicate that the peak force presents linear variation with the confining stress and an increasing trend with the bedding inclination at the first penetration, and the failure mode of the second penetration is mainly related to the broken status from the first penetration.